On the issue of improving the mechanism of electronic evidence in forensics - Esimbetova, B (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
This article highlights some of the issues of forensic tactics used in the study of digital data from any device that can process, store or transmit data in any form